A study on the fabrication of plasticized polystyrene-carbon nanotube nanocomposites for foaming. (May 2018) - McCrary-Dennis, Micah CL; Fernandez, Eduardo; Okoli, Okenwa I
The impregnation of carbon nanotubes within fiber-reinforced polymers (FRPs) is a sought after capability for the advancement of composite systems. This study evaluates the novel processing of a carbon nanotube nanocomposite that has been developed to incorporate varying carbon nanotube loadings within final composite foams. This material is manufactured through a melt mix process of carbon nanotubes and polystyrene at ∼2.0–13.0 wt.% that further underwent a plasticization process in an acetone solvent. The chemical foaming agent 2.2′-Azobi(isobutyronitrile) is used to facilitate foaming at a constant 3.0 wt.% concentration. The foamed nanocomposite results in a carbon nanotube-loaded micro-porous structure showing capabilities of delivering localized carbon nanotube placement within fiber composite laminate systems. This report's aim is to illustrate the effects of plasticizing polystyrene-carbon nanotube nanocomposite and calendaring the softened material to form foams imbedded with carbon nanotubes (carbon nanotubes). Scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis, and Fourier transform infrared spectroscopy were the tools that are used to characterize the materials at the various morphologies with their findings inclusive.